Apprentissage semi-autonome: Résultats d’une expérience de tutorat - WILCZYŃSKA, Weronika (My University, 1999)
The contribution reports some results from a study on the semi-autonomous learning of French as a foreign language by a dozen of first-year university students (intermediate level). It focuses on the evolution those students, identified as « poor learners », underwent as far as their views, attitudes and strategies in FL learning were concerned - as an effect of them being helped and advised by their much more advanced colleagues (4th year). By the end of this period the 1st year students showed a clear change in all these respects, even though adapting more adequate strategies proved slower to appear than changes in views and attitudes. At the same time, the experience proved to be most fruitful to their tutors in acquainting them with action research methodology.